Analisis Kemampuan Bahasa Anak Usia 5-6 Tahun di TK Negeri Pembina Kec. Pancur Batu - Tarigan, Ekayanti (Yayasan Pendidikan Internasional Bengkulu, 2022)
Language skills in early childhood are a basic need for children to communicate with teachers and friends. By being able to speak spoken and written language, students can follow learning at school. Of course, with fun learning designed by the teacher, it can optimally encourage children's language skills. The focus of this study was to analyze the language skills of children aged 5-6 years at Pembina Pancur Batu State Kindergarten T.A 2022/2023. With the results of this analysis, teachers can design learning that supports improving children's language skills. This research is a qualitative descriptive research with a case study approach to collect information related to children's language skills. The results showed that the category of children's language skills was quite good with a percentage of 69.79%. This means that teacher learning strategies are still needed to improve the quality of learning that supports the improvement of children's language skills in the school.